2019
DOI: 10.7759/cureus.4673
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Congenital Heart Disease in Newborns with Prenatal Exposure to Anti-depressant Medications

Abstract: Introduction It is uncertain whether the use of selective serotonin-reuptake inhibitors (SSRI) and other anti-depressants during pregnancy is associated with an increased risk of congenital heart disease (CHD) in newborn. There have been various studies showing a number of adverse outcomes, including gestational hypertension, reduced birth weight, altered neonatal pain responses and persistent pulmonary hypertension of the newborn with exposure to anti-depressant medications. There have been very fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Along with our study, other research has shown that cultural issues, including the consequences of an unhealthy\ lifestyle, are important in CHD. Mothers who often had unwanted pregnancies and used various drugs during pregnancy were at higher risk of giving birth to children with CHD [ 50 , 51 ]. According to the findings, the lifestyle of mothers with CHD children was far from health awareness, and going to a doctor or following medical measures was not important for them.…”
Section: Discussionmentioning
confidence: 99%
“…Along with our study, other research has shown that cultural issues, including the consequences of an unhealthy\ lifestyle, are important in CHD. Mothers who often had unwanted pregnancies and used various drugs during pregnancy were at higher risk of giving birth to children with CHD [ 50 , 51 ]. According to the findings, the lifestyle of mothers with CHD children was far from health awareness, and going to a doctor or following medical measures was not important for them.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of success in translating current preclinical drug trials into clinical practices can partly be attributed to (1) lack of adequate models of human FMi or impracticality to sample these tissues for studies during pregnancy, (2) placental perfusion studies are restricted to the placental–decidual interface, and drugs passage through the fetal membrane–decidual interface is not tested, confounding data and causing disruptions in clinical trials, (3) anatomical and endocrinological differences between most animal models and humans, and (4) not having studied fetal membrane–decidual FMi’s drug transport functions. In addition, many drugs currently cannot be used during pregnancy as their adverse effects on pregnancy are either unknown or cannot be easily tested. …”
Section: Introductionmentioning
confidence: 99%
“…Serotonin plays an important role as a signaling molecule in several aspects of the development of an embryo including the genesis of the heart. In children exposed to SSRIs during the first trimester, an increased risk of septal defects, and also specifically atrial septal defects was observed in several studies 25,[42][43][44][45][46][47][48] . The same applies to selective serotonin norephedrine reuptake inhibitors (SSNRIs) 25,49 .…”
mentioning
confidence: 98%